Eco-awareness as an antithesis of apocalyptic eco-phobia in Margaret Atwood’s (The Year of the Flood) - Yahya Al-Sammarraie, Amani Akram; Kaur, Hardev; Baha, Idar Baizura (Deanship of Academic Research, University of Jordan, 2022)
This paper argues that eco-awareness is presented in Margaret Atwood’s The Year of the Flood as a remedy for apocalyptic eco-phobia. The study focuses on apocalypse and eco-phobia as a motivation of the characters’ eco-awareness. Accordingly, the novel depicts several scenes of natural apocalyptic regarding the decline of the environment. There is an obvious relationship between apocalyptic eco-phobia and eco-awareness because they are environmental elements. Therefore, the study examines Atwood’s perception of apocalypse that threatens the ideal nature; she offers alternatives to avoid it via elevating the characters’ eco-awareness. Consequently, eco-awareness exemplifies the ideal natural state needed by the characters because imminent apocalypse endangers its safety and significance to their lives. Here, the study scrutinizes eco-awareness as a remedy for possible destructive environmental disaster. Hence, it applies Scott Slovic’s concept of eco-awareness as a remedy for apocalyptic eco-phobia to unravel Atwood’s obsession with contemporary negative exploitation of nature. By interpreting the contradiction between eco-awareness and apocalyptic eco-phobia, it tries to contend that environmental perfection would exacerbate the characters’ eco-awareness. The novel encourages readers to deduce the vitality of eco-awareness and its capacity to promote the characters’ need for ideal environment. This finding accentuates the characters engagement with nature since it exalts their eco-awareness as a therapeutic antithesis to apocalyptic eco-phobia; whereby they become convened to cease exploiting nature in negative way. Thus, the study explores how Atwood’s descriptive portrayal of natural apocalypse prompts the characters’ eco-phobic feelings; and how it could be mitigated by dint of their eco-awareness